The gospel & racial reconciliation - Moore, Russell, 1971-; Walker, Andrew, 1945- (Nashville, Tennessee : B & H Publishing Group, 2016)
In the Kingdom of God, it is not Us against Them. The problem of racism stretches back as far as humanity's origin in the book of Genesis. Brother pitted against brother, tribe against tribe-- people have warred against one another, fueled by contempt for racial differences. Yet the gospel is a message of reconciliation. The Kingdom of God is us reconciled to one another. - back cover.
What are we for? / J. Daniel Hays -- What does the gospel say? / Thabiti Anyabwile -- How should the Christian live? / Trillia Newbell -- How should the church engage? / Eric Mason -- What does the culture say? / Matthew J. Hall and D.A. Horton.
Keywords: Reconciliation -- Religious aspects -- Christianity; Race discrimination -- Religious aspects -- Christianity